2020
DOI: 10.1042/bsr20193917
|View full text |Cite
|
Sign up to set email alerts
|

Serum levels of superoxide dismutases in patients with benign paroxysmal positional vertigo

Abstract: Objective: To investigate the possible role of superoxide dismutases (SODs) in the development of benign paroxysmal positional vertigo (BPPV) and recurrence events in a 1-year follow-up study. Methods: This was a prospective one-center study. A total of 204 patients with BPPV and 120 age-and sex matched healthy subjects were included. The levels of SOD between patients and control cases were compared. The levels of SOD between posterior semicircular canal (PSC) and horizontal semicircular canal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 32 publications
0
11
0
1
Order By: Relevance
“…The role of oxidative stress in BPPV has been demonstrated with increased expression of VCAM-1 and d-ROM, which confirms angiitis’s existence and supports vascular involvement in BPPV [ 44 , 45 , 46 ]. Furthermore, identifying high levels of d-ROM and VCAM-1 could suggest the usefulness of a drug treatment aimed at correcting oxidative stress and activating endothelial cells [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 68%
“…The role of oxidative stress in BPPV has been demonstrated with increased expression of VCAM-1 and d-ROM, which confirms angiitis’s existence and supports vascular involvement in BPPV [ 44 , 45 , 46 ]. Furthermore, identifying high levels of d-ROM and VCAM-1 could suggest the usefulness of a drug treatment aimed at correcting oxidative stress and activating endothelial cells [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 68%
“…There are studies explaining that the inflammatory process and oxidative stress formation play a role in the development of vertigo [ 17 ]. İn a study, researchers indicated that calcium metabolism and its relationship with oxidative stress may play a role in the development of BPPV [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ishiyama et al proposed that migraine causes recurrent vasospasms that damage the vasculature of the inner ear, which may in turn displace the otoconia from the otolith organs [ 13 ]. This connection is further supported by the fact that repeated vasospasms cause oxidative stress, and decreased levels of superoxide dismutase (SOD), an antioxidant protein, have been observed in both migraine and BPPV [ 16 - 18 ]. Additionally, calcitonin gene-related peptide (CGRP), a neuroactive peptide that is released by trigeminal nerves during migraine attacks [ 19 ], may represent another pathophysiological link.…”
Section: Discussionmentioning
confidence: 99%